KONSERVASI WADAH KUBUR (SORONGA) DI MUSEUM PROVINSI SULAWESI TENGGARA - Yasni Yasni; Abdul Alim; Sandy Suseno (SANGIA JOURNAL OF ARCHAEOLOGY RESEARCH, 2019)
The purpose of this study was to determine the factors of damage and know how to overcome Soronga damage in the museum of Southeast Sulawes i Province. The method used is a type of qualitative research. Data collection methods used are divided into two namely collection of library data (secondary) and data field data (primary) namely direct observation. The field data collection was carried out by interviewing, documenting and analyzing damaging factors and analyzing the protection of Soronga collections in the museum of Southeast Sulawesi Province. Based on the results of the study, Soronga (primary burial) found in the State Museum of Southeast Sulawesi Province is a tomb container made of wood and used by the King (Mokole) in the Pre-Islamic era shaped like a boat. In general the Tolaki people in North Kolaka know the burial system, namely direct burial (primary burial). There are 4 factors that cause damage to Soronga and 6 countermeasures for protection of Soronga grave containers from damage such as: 1. Mechanical physical force, 2. Incorrect Relative Use, 3. Pests (insects, rodents and birds), 4. Dosiation ( carelessness of the officer). And 6 forms of protection in the museum exhibition building in Southeast Sulawesi Province, namely: 1. Objects, 2. Vitrine, 3. Showrooms, 4. Property / Facilities, 5. Building, 6. Procedures.